Peripheral cellular and humoral responses to infestation with the cattle tick Rhipicephalus microplus in Santa Gertrudis cattle. (January 2017) - Piper, E. K.; Jonsson, N. N.; Gondro, C.; Vance, M. E.; Lew‐Tabor, A.; Jackson, L. A.
Summary: Resistance to cattle tick infestation in single‐host ticks is primarily manifested against the larval stage and results in the immature tick failing to attach successfully and obtain a meal. This study was conducted to identify immune responses that characterize the tick‐resistant phenotype in cattle. Thirty‐five tick‐naïve Santa Gertrudis heifers were used in this study, thirty of which were artificially infested for thirteen weeks with tick larvae while five animals remained at a tick‐free quarantine property to serve as a control group. Following thirteen weeks of tick infestation, the animals in this trial exhibited highly divergent tick‐resistant phenotypes. Blood samples collected throughout the trial were used to measure peripheral immune parameters: haematology, the percentage of cellular subsets comprising the peripheral blood mononuclear cell (PBMC) population, tick‐specific IgG1 and IgG2 antibody titres, IgG1 avidity for tick antigens and the ability of PBMC to recognize and proliferate in response to stimulation with tick antigens in vitro. The tick‐susceptible cattle developed significantly higher tick‐specific IgG1 antibody titres compared to the tick‐resistant animals. These results suggest that the heightened antibody response either does not play a role in resistance or might contribute to increased susceptibility to infestation.